Management of chronic non-cancer pain in Swiss nursing homes: an observational mixed-methods study - Florent Macé; Marion Yerli; Damien Cateau; Tosca Bizzozzero; Isabelle Levasseur; Anne Niquille (Swiss Medical Weekly, 2026)
STUDY AIMS: The management of chronic non-cancer pain in nursing home residents represents a major challenge, given the complexity and fragility of this population. The aim of this study was to evaluate professional practice in this management in nursing homes of the French-speaking part of Switzerland. METHODS: Our observational study was based on a panel of 124 nursing homes in the Vaud canton. Two convergent parallel approaches were carried out to collect data: an online questionnaire for nurses and referring physicians about the chronic pain management practices of their nursing home, as well as a retrospective observational study analysing analgesic consumption in nursing homes of the Vaud canton between 2017 and 2021. RESULTS: Our study highlights that mixed pain evaluation (self- and hetero-assessment) and non-pharmacological measures (i.e. physiotherapy, psychological and adapted physical activities) are used in the management of chronic non-cancer pain within the studied nursing homes. Opioid analgesics are mainly considered when non-pharmacological measures and step 1 analgesics are insufficient to manage the pain. When an opioid analgesic is considered, tramadol and morphine are the most frequently prescribed drugs among step 2 and 3 analgesics. Collaboration between nurses and physicians in pain management is evaluated as good or excellent by most interviewees, with mutual recognition of each other’s professional role. The pharmacist’s role seems more limited, mainly to providing reminders of best prescribing practices for analgesics during quality circle sessions, and routinely verifying the adequacy of analgesic treatments prescribed. The lack of time at the resident’s bedside, the nurses’ specific skills in pain management, and the reluctance of patients to report their pain were the main obstacles mentioned by the interviewed professionals. A disparity between nursing homes was observed in terms of quantitative and qualitative consumption of analgesics. CONCLUSION: This study shows that healthcare professionals in nursing homes considered are aware and adhere to recommendations for chronic non-cancer pain management, whether in terms of pain assessment, or non-pharmacological and pharmacological measures. This management is supported by interprofessional practice within these nursing homes, in terms of defining the roles of each and sharing tasks between physicians and nurses. However, a strengthening of the interprofessional collaboration, a more extensive training of nurses as well as audit and feedback on analgesic use would be levers to foster better management of chronic non-cancer pain among nursing home residents.